Structural Investigation on Curcumin - GUNASEKARAN, S.; NATARAJAN, R.K.; NATARAJAN, S.; RATHIKHA, R. (Asian Journal of Chemistry, 2010)
Curcumin is non nutrient (phytochemical) extracted from Curcuma longa L. (Turmeric). Owing its antitumour and anticancer activities, its importance in the pharmacology field has been escalating. For better understanding on the photobiology of curcumin and its derivatives namely curcuminoids, their spectral, photophysical and photochemical behaviours are to be investigated. This study has been aimed to obtain detailed structural information on the curcumin through its spectral behaviour. For this, a variety of spectra such as UVVisible, FTIR and NMR have been recorded for the pure curcumin. From the UV-Visible spectral data, different chromophore moieties have been identified for the curcumin molecule. FTIR spectral data gives a wealth of information on the different functional groups of the curcumin molecule. NMR is preeminent technique that has helped in solving the ketoenolic tautomerism of curcumin and deciphering the enolic form of the molecule. Also, a host of thermodynamic properties have been obtained for the molecule by molecular mechanics (MM3) methods.